Hidden aspects of social entrepreneurs' life: A content analysis - Ruchita Pangriya (Journal of Global Entrepreneurship Research, 2019)
Social entrepreneurship has been defined as entrepreneurship with a social goal; social entrepreneur is a change agent. Literature shows that social entrepreneurship is treated as a youthful field of study and needs thorough observational appraisals to develop, which proposes a plenitude of research openings (Hoogendoorn, Pennings, & Thurik, ERIM Report Series Reference No. ERS-2009-044-ORG, 2010; Hand & Lewis, Stanford Social Innovation Review, 2016). The work on social entrepreneurship is on the rise; however, little attention was given to the traits and motivational factors for social entrepreneurs. To fill this gap, this study explores the traits and motivations of social entrepreneurs. A content analysis technique has been used to analyse the data. The interviews, speeches and articles on nine social entrepreneurs were analysed. The results indicate education, global exposure, prior work experience, creativity, empathy, community roots and contentment were the main characteristics of a social entrepreneur. Self-transcendence, unique ideas and innovation to solve pain points, inspiration and personal experience motivate an individual to become a social entrepreneur. Findings of this study will contribute to the practical and research in the area of social entrepreneurship. The present research will contribute to the growing literature that attempts to explain the profile of a social entrepreneur and motivational factors.
Keywords: 650; Social entrepreneurship; Social business; Social enterprises; Motivation; Characteristics